Transitioning to university in Botswana: What developmental education intervention is timely for entry into STEM Baccalaureate degree programs? - Lyken-Segosebe, Dawn; Sparrow, Michael (Journal of Interdisciplinary Studies in Education, 2024)
Academic and social deficits, a nine-month secondary school-to-university learning loss, a readiness gap for university-level coursework, and limited cultural capital characterize the transition to university for Botswana’s secondary school completers seeking a STEM qualification. This study investigated internationally implemented developmental education interventions that STEM-offering public universities in Botswana may proactively implement to ease the transition and improve matriculant’s chances of success from their first year at university. Findings indicate that a Developmental Winter Bridge Program presents the best option for secondary school completers’ acclimatization, assimilation, and university success. Policy recognition of the Bridge Program as a pre-entry requirement for STEM undergraduate programs is recommended as the first step towards increasing confidence in the preparation of future-ready engineers and scientists.